2016
DOI: 10.1039/c6ce00764c
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal to single-crystal conformational polymorphic transformation in tolbutamide at 313 K. Relation to other polymorphic transformations in tolbutamide and chlorpropamide

Abstract: Three polymorphs of tolbutamide (I L , II, and III) were studied using single-crystal X-ray diffraction, from 100 K to room temperature (forms II and III) and to 350 K (form I), and differential scanning calorimetry. The reversible transformation, I L ⇔ I H , was found to be of the single-crystal to single-crystal type and the structure of the high-temperature form (I H) was solved and refined. The structure of I H differs from that of I L only in the conformation of the molecule, with molecular arrangements b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
3
19
1
Order By: Relevance
“…In this respect, tolazamide resembles methyl-2-(carbazol-9-yl)benzoate, 89 or 3-hydroxy-4,5-dimethyl-1-phenylpyridazin-6-one, 27 which becomes more ordered at high pressures, but differs radically from chlorpropamide or tolbutamide, in which the number of molecules with different conformations increases after the polymorphic transitions induced by increasing pressure, 22 or on varying the temperature. [90][91][92] Disorder in structure I was not observed at any of the elevated pressures studied in this work. It is important to note that disorder was taken into account for the aforementioned energy and enthalpy calculations (see "Computational details" in the ESI †), because calculations based on only one disordered form for any polymorph can lead to misleading energy calculations (e.g.…”
Section: Resultscontrasting
confidence: 47%
“…In this respect, tolazamide resembles methyl-2-(carbazol-9-yl)benzoate, 89 or 3-hydroxy-4,5-dimethyl-1-phenylpyridazin-6-one, 27 which becomes more ordered at high pressures, but differs radically from chlorpropamide or tolbutamide, in which the number of molecules with different conformations increases after the polymorphic transitions induced by increasing pressure, 22 or on varying the temperature. [90][91][92] Disorder in structure I was not observed at any of the elevated pressures studied in this work. It is important to note that disorder was taken into account for the aforementioned energy and enthalpy calculations (see "Computational details" in the ESI †), because calculations based on only one disordered form for any polymorph can lead to misleading energy calculations (e.g.…”
Section: Resultscontrasting
confidence: 47%
“…Some of them were increased significantly ( P < 0.05) during IF (Table 4) including stavudine (Nayak, Boxi, Ashe, Thathapudi, & Nayak, ), ketoprofen, d ‐biotin, baclofen, capecitabine, rosiglitazone, and tolbutamide. The health benefits of tea are improved due to pharmacological components produced in fermentation, which includes in improving rheumatoid arthritis (Zafar et al., ), arthrolithiasis (Takara et al., ; Zafar et al., ), anticancer (Leicher, Graal, Coers, Tascilar, & Groot, ) and diabetes treatment (Drebushchak, Drebushchak, Pankrushina, & Boldyreva, ). Moreover, no harmful ingredients were identified in collected samples from IF, which showed that A. sydowii was a strain with high safety and had great potential applications in fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Through the crystal structure analysis, we found that the introduction of MET had a big impact on the molecular structure of tolbutamide. Before this study, five polymorphs (I, II, III, IV and V) (Drebushchak et al, 2016;Nath & Nangia, 2011;Thirunahari et al, 2010) and two salts (the n-butylammonium and piperazinium salts) (Drebushchak et al, 2013;Samie et al, 2017) of TOL had been reported. The conformers in these polymorphs can be divided into two types based on the orientation of the phenyl and alkyl tails, i.e.…”
Section: Single-crystal Structure Analysismentioning
confidence: 98%